Strength, Carbonation Resistance, and Chloride-Ion Penetrability of Cement Mortars Containing Catechol-Functionalized Chitosan Polymer - Se-Jin Choi (MDPI AG, 2021)
There have been numerous recent studies on improving the mechanical properties and durability of cement composites by mixing them with functional polymers. However, research into applying modified biopolymer such as catechol-functionalized chitosan to cement mortar or concrete is rare to the best of our knowledge. In this study, catechol-functionalized chitosan (Cat-Chit), a well-known bioinspired polymer that imitates the basic structures and functions of living organisms and biological materials in nature, was synthesized and combined with cement mortar in various proportions. The compressive strength, tensile strength, drying shrinkage, accelerated carbonation depth, and chloride-ion penetrability of these mixes were then evaluated. In the ultraviolet–visible spectra, a maximum absorption peak appeared at 280 nm, corresponding to catechol conjugation. The sample containing 7.5% Cat-Chit polymer in water (CPW) exhibited the highest compressive strength, and its 28-day compressive strength was ~20.2% higher than that of a control sample with no added polymer. The tensile strength of the samples containing 5% or more CPW was ~2.3–11.5% higher than that of the control sample. Additionally, all the Cat-Chit polymer mixtures exhibited lower carbonation depths than compared to the control sample. The total charge passing through the samples decreased as the amount of CPW increased. Thus, incorporating this polymer effectively improved the mechanical properties, carbonation resistance, and chloride-ion penetration resistance of cement mortar.